Slow habituation of arousal associated with psychosis proneness. - Allen, P; Freeman, D; McGuire, P (2007)
BACKGROUND: Previous studies report skin conductance (SC) abnormalities in both patients with schizophrenia and psychosis-prone individuals. However, no studies have assessed SC abnormalities in relation to specific psychotic and emotional symptoms. The aim of the present study was to examine the relationship between SC orienting response and hallucination proneness, delusional ideation, anxiety and self-focused attention in non-clinical individuals. METHOD: Forty-three participants were recruited and divided into two groups depending upon the SC habituation profile. Normal habituators (n=28) and slow habituators (n=15) were compared on measures of psychosis proneness, anxiety and self-focused attention. RESULTS: Slow habituators had significantly higher levels of delusional ideation and hallucination proneness than the normal habituators. SC habituation scores were particularly associated with the conviction of delusional ideas. Levels of anxiety or self-focused attention did not differ significantly between the groups. CONCLUSIONS: The study provides evidence of 'aetiological continuity'. Common mechanisms may contribute to psychotic experiences in non-clinical and clinical samples, consistent with the notion of a psychosis continuum.